The antioxidant effect of triptolide contributes to the therapy in a collagen-induced arthritis rat model. (1st January 2021) - Yu, Guang-Min; Zhou, Li-Feng; Zeng, Bi-Xia; Huang, Jing-Jun; She, Xiao-jun
ABSTRACT: Background: As a chronic autoimmune disease, rheumatoid arthritis (RA) is related to oxidative stress, which may lead to the occurrence and persistence of inflammation in RA. The purpose of this study is to evaluate the potential antioxidant effect of triptolide in collagen-induced arthritis (CIA) rat model. Methods: We examined the severity of arthritis, levels of local and systemic oxidative stress, periarticular bone erosion and weight of organs in CIA rats treated with triptolide. Results: We found that triptolide decreased the paw thickness and clinical arthritis score, significantly. The mRNA expression and activity of myeloperoxidase and inducible nitric oxide synthase were remarkably decreased in the paws of the CIA rats after triptolide treatment. Triptolide significantly inhibited the levels of nitrite and nitrate in serum, as well as the urinary level of dityrosine. Triptolide treatment also markedly increased bone volume of tibia, but suppressed epiphyseal plate thickness of both femur and tibia. In addition, there was no significant difference in the weight of organs after the therapy, except decreased spleen weight. Conclusions: These results suggested that the local and systemic oxidative stress was enhanced in the CIA rats and the therapeutic dose of triptolide had a definite antioxidant effect.